A Structuralist Analysis of Binary Oppositions in Bella Swan’s Characterization in The Twilight Saga: New Moon - Nabila Rayati; Purwanto Siwi; Sempa Br. Perangin Angin; Doni Efrizah (Universitas Islam Sumatera Utara, 2026)
This study examines the characterization of Bella Swan as the protagonist in The Twilight Saga: New Moon (2009) through Lévi-Strauss’s structuralist theory, particularly the concept of binary opposition. By focusing on narrative and symbolic contrasts, the analysis explores how meaning is constructed within the protagonist’s development. A qualitative descriptive method is applied through the analysis of selected scenes and dialogues from the film. The findings indicate that Bella Swan’s characterization is shaped by dominant binary oppositions, including love versus loss, courage versus fear, humanity versus the supernatural, and Edward versus Jacob. These oppositions position her as a structural protagonist who embodies emotional and ideological tensions within the narrative. She also functions as a mediating figure between conflicting value systems, reflecting the dynamic and relational nature of identity construction in cinematic texts. Unlike previous studies that emphasize romantic themes or surface-level character analysis, this research highlights the underlying structural system that actively constructs the protagonist’s identity. The findings contribute to literary and film studies by demonstrating how meaning in film can be systematically interpreted through Lévi-Straussian structuralism.